2014
DOI: 10.4103/1305-7456.143609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term repeated topical fluoride applications and adhesion promoter on shear bond strengths of orthodontic brackets

Abstract: Objective:The purpose of this study was to assess the effects of long-term repeated topical application of fluoride before bonding and an adhesion promoter on the bond strength of orthodontic brackets.Materials and Methods:A total of 76 bovine incisors were collected and divided equally into four groups. In group 1, the brackets were bonded without topical fluoride application or adhesion promoter. In group 2, before bonding, the adhesion promoter was applied to nonfluoridated enamel. In group 3, the brackets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
4
2
0
Order By: Relevance
“…This result was consistent with the experiments by Bayrak et al [20] and Endo et al, [21] in which fluoride varnish was applied before bracket attachment to human tooth samples using RMGIC bonding agent. Nonetheless, this result was inconsistent with a study by Nhan et al, [22] in which fluoride varnish application did not contribute to the difference of shear strength of brackets bonded with composite resin bonding agent and phosphoric acid etch.…”
Section: Discussionsupporting
confidence: 92%
“…This result was consistent with the experiments by Bayrak et al [20] and Endo et al, [21] in which fluoride varnish was applied before bracket attachment to human tooth samples using RMGIC bonding agent. Nonetheless, this result was inconsistent with a study by Nhan et al, [22] in which fluoride varnish application did not contribute to the difference of shear strength of brackets bonded with composite resin bonding agent and phosphoric acid etch.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, medium and low viscosity IDBSs with the adhesion promoter had lower frequencies of bond failure at the enamel-adhesive interface than those without this promoter, as shown in a previous study 24) . These results may be caused by the speculation that the combination of adhesion promoter and the BOB SEP moderately demineralizes enamel and enhances mechanical bonding between the adhesive and enamel surface, as previously mentioned.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, in all three IDBSs, application of an adhesion promoter containing polyacrylic acid gave a significantly higher SBS than in the case of nonapplication of this promoter. Some studies have shown that adhesion promoters significantly increase SBSs 7,8,24) , as evidenced by this study, while others showed that any adhesion promoters did not significantly increase the SBS 25) . Es-souni et al 26) reported that polyacrylic acid leached calcium and phosphorus from hydroxyapatite, and formed a fine polymeric film on the enamel surface.…”
Section: Discussionsupporting
confidence: 60%
“…Based on these previous findings, our result showing that the RMGIC system (group 1, 11.7 MPa) exhibited a significantly higher mean SBS than the BOB system combined with the self-etching primer (group 2, 9.6 MPa) might be expected. In both the RMGIC system and BOB system combined with the self-etching primer, the chemical bonding mechanism between the adhesive and buccal enamel is considered to be superior to mechanical adhesion 15,16) . This is consistent with our SEM findings that buccal enamel treated with both 10% polyacrylic acid (Fig.…”
Section: Discussionmentioning
confidence: 99%